2021
DOI: 10.3389/fphar.2021.651267
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Small-Conductance, Ca2+-Activated K+ Current by Ondansetron

Abstract: Background: Small-conductance Ca2+-activated K+ channels (SK channels) have been proposed as antiarrhythmic targets for the treatment of atrial fibrillation. We previously demonstrated that the 5-HT3 receptor antagonist ondansetron inhibits heterologously expressed, human SK2 (hSK2) currents as well as native cardiac SK currents in a physiological extra-/intracellular [K+] gradient at therapeutic (i.e., sub-micromolar) concentrations. A recent study, using symmetrical [K+] conditions, challenged this result. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was also reported that SK2 current in hypertrophied rat ventricle was upregulated by CaMKII [85]. Recently, inhibition of SK2 current in the submicromolar range was reported by ondansetron [86], and it was found that it increased vulnerability to ventricular fibrillation in a failing rabbit heart [87].…”
Section: Remodeling Of Repolarizing Transmembrane Currents In Hfmentioning
confidence: 95%
“…It was also reported that SK2 current in hypertrophied rat ventricle was upregulated by CaMKII [85]. Recently, inhibition of SK2 current in the submicromolar range was reported by ondansetron [86], and it was found that it increased vulnerability to ventricular fibrillation in a failing rabbit heart [87].…”
Section: Remodeling Of Repolarizing Transmembrane Currents In Hfmentioning
confidence: 95%